Built to be CEO a woman's journey to the top - Sabrina, Ghouse (Independently published, 2019)
We live in a world where women make up half of the population, but only 5% of Fortune 500 CEOs. While the wage gap is slowly closing, studies show we will not reach gender pay equity until 2053. As women enter the business world in bigger numbers, Hollywood lags behind in featuring women in important roles. We can all agree on one thing: to change this, we need more women in leadership positions. In my short career, I have served many CEOs, mostly as a Chief of Staff. I have learned how to navigate pervasive gender stereotypes and build valuable technical skills and personal traits. In this book, I will share the most important lessons with you ? the ones that pertain to creating future CEOs. For those of you who have considered aiming for the role, I am here to provide you with advanced career advice on how to get to the top. For those of you who have not yet decided what you'd like to be, I am here to convince you: YOU are built to be CEO.
Keywords: Leadership